SPATIAL AND TEMPORAL VARIABILITY OF SEA SURFACE TEMPERATURE AND CHLOROPHYLL-A ACCORDING TO THE SEASON IN PESISIR SELATAN REGENCY WATERS WITH AQUA-MODIS IMAGERY - Hendra Saputra (International Remote Sensing Applied Journal, 2020)
Fishermen's understanding of oceanographic parameters, especially sea surface temperature conditions and chlorophyll-a concentration in the process of determining fishing operations are still very low. The cause is the constraints of technology and human resources, and not widely available data and information on fisheries resources, including their parameters. Remote sensing technology is one solution that can be used to understand the spatial and temporal conditions of great waters. This research was conducted in the waters of the Pesisir Selatan Regency with the aim to : 1) measure and map the spatial and temporal variability of sea surface temperature in 2013, 2) measure and map the spatial and temporal variability of chlorophyll-a concentration in 2011-2013, 3) measure the relationship between sea surface temperature with the concentration of chlorophyll-a. This study uses a quantitative approach using analysis desk metode. The results showed that: 1) sea surface temperature mean highest monthly throughout the year occurred in the first transitional season between March and May, where sea surface temperatures reach more than 31 0C, 2) Chlorophyll-a concentration between 2011 to 2013 was highest in the east of the season and second in the transitional seasons are concentrated in the area of the waters region of Linggo Sari Baganti Regencys to Silaut Regencys, 3) Sea surface temperature is strongly influencing the concentration of chlorophyll-a, regression coefficient (r) of 0.811, Relationships sea surface temperatures mean monthly negatively correlated, with each increase of 1 0C of the sea surface temperature caused a decrease in chlorophyll-a concentration of 0.176 mg/m3.